I would use substitution.
So y=x-1 and 2x+y=8
Substitute y=x-1 in for y
2x+(x-1)=8
Simply
= 3x -1=8
Bring the one to the other side
3x=9
Divide
X=3
Plug x into y=x-1
Y=(3)-1
Y=2
Check with the other equation
2(3)+(2)=8
6+2 =8
X=3
Y=2
You can also do elimination.
Y=x-1 and 2x+y=8
Subtract c from the first equation
-x+y=-1 and 2x+y=8
Those are your equations.
-1(-x+y)=-1
= x-y=1
2x+y=8
The y’s would cancel and you would add down so this is your new equation
3x=9
X=3
You then plug in the 3 for x
And find y
Y=(3)-1
Y=2